2015
DOI: 10.1007/s00402-015-2342-3
|View full text |Cite
|
Sign up to set email alerts
|

Early recovery after arthroscopic repair compared to open repair of the anterior talofibular ligament for lateral instability of the ankle

Abstract: Compared with the open procedure, arthroscopic ATFL repair with IER reinforcement for LIA had an equivalent clinical result at the 1-year follow-up and allowed early recovery after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 21 publications
3
90
0
1
Order By: Relevance
“…Without external supports, the elapsed time between injury and return to full athletic activity was 16.0 weeks (F) and 10.1 weeks (RF) (p<0.0001). Matsui et al 26 compared arthroscopic (A) and open (O) repairs, and found no significant difference in mean time to return to sports activities for the two groups (16.5 weeks (A) vs 17.1 weeks (O); p=0.07). Yoo and Yang38 compared arthroscopic Broström with an internal brace to arthroscopic Broström without an internal brace.…”
Section: Resultsmentioning
confidence: 99%
“…Without external supports, the elapsed time between injury and return to full athletic activity was 16.0 weeks (F) and 10.1 weeks (RF) (p<0.0001). Matsui et al 26 compared arthroscopic (A) and open (O) repairs, and found no significant difference in mean time to return to sports activities for the two groups (16.5 weeks (A) vs 17.1 weeks (O); p=0.07). Yoo and Yang38 compared arthroscopic Broström with an internal brace to arthroscopic Broström without an internal brace.…”
Section: Resultsmentioning
confidence: 99%
“…We noticed that the patients in Yeo, Li, and Rigby' studies [15,17,18] involved several different accompanying intra-articular pathologies such as synovitis, anterior tibial spur, loose body, and OLTs. Matsui [16] and Zeng [19], however, enrolled only the patients without intra-articular lesions. To the authors' best knowledge, our comparison is the first study that compared the results between the arthroscopic and the open surgery in patients of lateral ankle instability accompanied by OLTs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the postoperative recovery seemed to be heavily influenced by the healing process of OLT. The patients who underwent only ATFL repair were encouraged to start ROM exercises and partial weight-bearing from the second day after surgery [16,28], while for patients of OLT, the 3rd to the 8th week after surgery is regarded as the remodeling phase of OLT healing. In this period, the mesenchymal cells proliferate and differentiate into chondrocytelike cells, which can produce a matrix containing type II collagens and proteoglycans [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations